Thermal Characteristics of a Rotating Closed-Loop Pulsating Heat Pipe Affected by Centrifugal Accelerations and Numbers of Turns / Niti Kammuang-lue ...[et al.] - Niti, Kammuang-lue; Kritsada, On-ai; Phrut, Sakulchangsatjatai; Pradit, Terdtoon (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Objective of this study is to experimentally investigate the effect of centrifugal accelerations and numbers of turns on thermal characteristics of the rotating closed-loop pulsating heat pipe (RCLPHP). The RCLPHPs were made of a copper tube with internal diameter of 1.50 mm and bent into flower’s petal-shape and arranged into a circle with 11, 22 and 33 turns. The evaporator section located at the outer end of the bundle while the condenser section placed around the center of the RCLPHP with no adiabatic section. Both sections had an identical length of 50 mm. R123, and ethanol was filled as working fluid respectively. The RCLPHP was installed on the test rig and it was rotated by the DC motor at the centrifugal acceleration of 0.5, 1, 3, 5, 10, and 20 times of the gravitational acceleration considering at the connection between the evaporator and condenser sections. Heat input was generated by electrical annular-plate heaters and varied from 24 to 42, 86, 132, and 174 W. Ceramic papers, wooden plate, and insulation sheet were consecutively attached on the outer side of the heaters in order to prevent the heat loss from the heater. It can be concluded that when the centrifugal acceleration increases, the thermal resistance per a unit area continuously decreases since the condensate flows back to the evaporator section more rapidly. Moreover, it can be found that when the number of turns increases, the absolute thermal resistance obviously decreases. On the other hand, the thermal resistance per unit area continuously increases as the increasing in the number of turns, since the friction loss due to the increase in the total length of the tube and in the number of the U-tube section retards the working fluid’s circulation to be less active.